Producing Plant Virus Patterns with Defined 2D Structure. Issue 18 (29th July 2021) - Müller-Renno, Christine; Remmel, Diana; Braun, Mario; Boonrod, Kajohn; Krczal, Gabi; Ziegler, Christiane
Abstract : In nanobiotechnology, viral nanoparticles have come into focus as interesting nano building blocks. In this context, the formation of 2D and 3D structures is of particular interest. Herein, the creation of defined 2D patterns of an icosahedral plant virus, the tomato bushy stunt virus (TBSV), by means of different techniques is reported on: the top‐down lithography ebeam and focused ion beam (FIB) as well as the bottom‐up fluidic force microscope (FluidFM) approach. The obtained layer structures are imaged by scanning force and scanning electron microscopy. The data show that a defined 2D structure can successfully be created either top down by FIB or bottom up by FluidFM. Electron beam lithography is not able to remove viruses from the substrate under the chosen conditions. FIB has an advantage if larger areas covered with viruses combined with smaller areas without being desired. FluidFM is advantageous if only small areas with viruses are required. A further benefit is that the uncovered areas are not affected. The pattern formation in FluidFM is influenced not only by the spotting parameters, but in particular by the drying process. Deegan and Marangoni effects are shown to play a role if the spotted droplets are not very small. Abstract : Patterns of virus particles are produced by focused ion beam (FIB) top‐down lithography and by the fluidic force microscope (FluidFM) bottom‐up approach. FIB is preferable if large virus coverages are required with small patterns without, whereas FluidFM is advantageous if small virus structures are desired. In FluidFM, not only the writing but also the drying process plays a vital role.